2017
DOI: 10.1061/(asce)is.1943-555x.0000350
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Testing Methods for Underwater Tunnel Linings: Practical Application at Chesapeake Channel Tunnel

Abstract: A field evaluation of an underwater tunnel is conducted using a variety of nondestructive testing (NDT) methods including visual inspection, air-and ground-coupled ground penetrating radar (GPR), ultrasonic tomography (UST), and impact echo (IE). An air-coupled GPR antenna is used along with visual inspection to identify areas of interest in the Chesapeake Channel Tunnel near Norfolk, Virginia. After an example potential damage area is identified using high-speed air-coupled GPR, a robotic scanner was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…We only encountered two research groups directly applying UST to tunnel subsurface inspection. In [28], UST is extremely time-inefficient, requiring 9-25 min to scan 1m of tunnel wall and necessitating use of a preliminary GPR scan (Section 3.6) to localise suspected features. Likewise, despite robotic automation, UST scans performed by tunnel profiler ROBOSPECT achieve comparably inefficient durations of one hour to scan 6m [29] and are optimised for surface level crack and spall detection only [30,31].…”
Section: Acoustic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We only encountered two research groups directly applying UST to tunnel subsurface inspection. In [28], UST is extremely time-inefficient, requiring 9-25 min to scan 1m of tunnel wall and necessitating use of a preliminary GPR scan (Section 3.6) to localise suspected features. Likewise, despite robotic automation, UST scans performed by tunnel profiler ROBOSPECT achieve comparably inefficient durations of one hour to scan 6m [29] and are optimised for surface level crack and spall detection only [30,31].…”
Section: Acoustic Methodsmentioning
confidence: 99%
“…Trolley-Mounted [75][76][77] (Figure 4a)-Units commonly feature interchangeable aircoupled antenna of differing frequencies to facilitate trade-off between penetration depth and output image resolution [28]. However, motorisation is infrequent, scans are unidirectional (typically railbed only) and offer no protection to operatives; Radargrams (B-scans) traditionally convey survey output, which although encoding multiple feature characteristics (e.g., depth, extent, orientation, heterogeneity, etc.)…”
mentioning
confidence: 99%
“…Studies have shown that these methods can effectively detect defects in tunnel linings and achieve satisfactory detection results [6][7][8]. The combination of multiple techniques [9,10] can especially enhance the identification and localization of the defects. Among these methods, GPR, particularly vehicle-mounted GPR [11], is more efficient and widely used in high-speed railway tunnel inspections [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main influencing features for TTBTs have been comprehensively studied [ 24 ]. Ultrasonic tomography (UST) is a nondestructive testing technology for the detection of impairments in tunnel lining [ 25 , 26 ]. For lining surface defect detection, an autonomous robot with computer vision system has been developed to inspect tunnel crack and efflorescence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%